Customer Satisfaction During The Post Covid-19 Pandemic: Testing The Effect of Food Quality, Packaging, and Customer Trust - Ardyan, Elia; Tanus, Evelyn Destiana; Sani, Fadhil Ali; Marselinus, Sayrina Cantika (International Business Management - Universitas Ciputra, 2023)
This study aimed to assess the impact of food quality and packaging on consumer trust and satisfaction. This study received a total of 84 responses, according to data acquired through the distribution of online questionnaires. Using Partial Least Squares Structural Equation Modeling, the data was analyzed. The data is processed using version 8 of WarpPls. The findings of this study reveal that product quality and packaging have a significant impact on customer trust and satisfaction. In addition to these findings, this study demonstrates that high levels of trust during the COVID-19 pandemic will influence customer satisfaction